If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(y + 1) = 3 Reorder the terms: 5(1 + y) = 3 (1 * 5 + y * 5) = 3 (5 + 5y) = 3 Solving 5 + 5y = 3 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 5y = 3 + -5 Combine like terms: 5 + -5 = 0 0 + 5y = 3 + -5 5y = 3 + -5 Combine like terms: 3 + -5 = -2 5y = -2 Divide each side by '5'. y = -0.4 Simplifying y = -0.4
| Abs(-7a)=28 | | sin(40)=8/x | | sin40=8/x | | F(x)=-4x^2+16 | | 6W+193=55 | | x+12=m+32 | | 8x-6x+25=35 | | 6(t-4)=3t+3 | | 8-6x+25=35 | | N^2+9n+9=0 | | 3(p+4)=2p-7 | | 5x+89=29 | | 2u+91=27 | | -7+0.25m=7 | | 0.8x+23=-25 | | 2x+24=18 | | 0.8x+23=25 | | -16a+67=3 | | 7x-35-3x=2x-13 | | 2x+24=78 | | 5c+17=2 | | -7v+81=32 | | -7v+81=7 | | 9b+50=275 | | 5y-10=-35 | | 25+11.12b=47 | | -2h+7=45 | | 6(4x-6)+18=6 | | 3s+158=-16 | | 8(x-4)-18=22 | | 7t+55=-246 | | 3-4x=-7+6x |